KOMITMEN ORGANISASI DAN KEINGINAN BERPINDAH KERJA KARYAWAN PADA RUMAH SAKIT IBU DAN ANAK BUNDA BAHAGIA - Hilda Mutia Hanum; Andreasta Meliala (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2023)
Background: A frequent phenomenon in human resources (HR) is that many employees leave their jobs (turnover). Efforts to control and reduce employee turnover begin with eliminating the desire to change jobs (turnover intention). There are many causes of turnover intention, including job satisfaction, work environment, and organizational commitment. High organizational commitment is what every organization, especially hospitals, expects from their employees. RSIA Bunda Bahagia shows an increasing turnover rate until 2022 reaching 79.4%. That condition proves that the turnover rate is high because the ideal condition of the turnover standard is 5-10% per year, so it is necessary to improve better employee management to achieve hospital success.Objective: This study aims to describe organizational commitment and turnover intention and measure the relationship of employee organizational commitment to turnover intention at RSIA Bunda Bahagia.Methods: This type of research is an exploratory case study research with a single case research design with qualitative data presentation. This research was conducted for 2 to 3 months after Ethical Clearance was issued, which was conducted on 51 employees with the Three-Component Model (TCM) Employee Commitment Survey research instrument to measure organizational commitment and Turnover Intention Scale-6 (TIS-6) to measure turnover intention.Results: Twenty-eight (54.9%) employees had a high level of organizational commitment, and 32 (62.7%) employees had a low turnover intention. Spearman’s Rank Correlation test results on organizational commitment and turnover intention showed a p-value of 0.001 (<0.05) with a correlation coefficient of -0.442. Organizational factors, individual factors, and social factors in organizational commitment have a relationship to turnover intention.Conclusion: There is a significant unidirectional relationship between organizational commitment and turnover intention in employees of RSIA Bunda Bahagia, so management needs to increase organizational commitment in employees so that turnover intention rates decrease.